Influence of effluents from a Wastewater Treatment Plant on nutrient distribution in a coastal creek from southern Brazil - Santos,Isaac Rodrigues (2008)
The hypothesis that effluents treated through activated sludge process cause changes in nutrient biogeochemistry of receiving water bodies was investigated in Vieira creek, southern Brazil. Dissolved oxygen, suspended matter, and pH did not vary among the sampling stations. Nutrient, biochemical oxygen demand, and conductivity values were significantly higher downstream from the Wastewater Treatment Plant (WWTP) effluents. Further downstream, nitrate concentrations were higher due to ammonium nitrification, organic matter remineralization and/or the occurrence of unidentified sources. Per capita nutrient emission factors were estimated to be 0.16 kg P.yr-1 and 4.14 kg N.yr-1. Under pristine conditions, low N:P ratios were observed, which were significantly increased downstream due to the high ammonium input. The mixing zone of the nitrogen-rich waters from Vieira creek with the phosphorus-enriched waters from Patos lagoon estuary was considered under high risk of eutrophication. The results could be useful for planning and management of WWTP-effluent receiving waters in temperate regions from developing countries.